Mark Antony’s assault of Publius Clodius: Another look - Alexander, Dean (Ciceroniana On Line, 2024)
This paper re-examines Cicero’s claim that Mark Antony tried to kill Publius Clodius in 53 BC. By investigating the historical, political and particularly the persuasive contexts in which Cicero makes the claim, it will be argued that the orator is exaggerating and misrepresenting a minor encounter between the two men, but one that cannot have been a premeditated assassination attempt, as he portrays it in the Second Philippic. The motives adduced by modern scholars to explain Antony’s attempt are unconvincing and the ramifications for accepting Cicero’s mendacity significant.